The Paradoxical Role of Interleukin-10 in Systemic Lupus Erythematosus: A Correlational Study of Serum Levels and Disease Activity - Yuniza; Joneri, Alrahman; Legiran; Nova Kurniati; Eddy Mart Salim (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Systemic lupus erythematosus (SLE) is a multifaceted autoimmune disease where the cytokine Interleukin-10 (IL-10) exhibits a paradoxical role, functioning as both a potent anti-inflammatory mediator and a robust B-cell stimulator. The clinical significance of serum IL-10 as a biomarker of disease activity is a subject of intense debate, with conflicting reports in the literature. This study was designed to investigate this relationship within a specific Southeast Asian cohort. Methods: An observational, cross-sectional study was conducted at a tertiary referral hospital in Palembang, Indonesia, enrolling 48 adult patients with a confirmed diagnosis of SLE. Disease activity was quantitatively scored using the Mexican Systemic Lupus Erythematosus Disease Activity Index (MEX-SLEDAI). Serum IL-10 concentrations were precisely measured using a quantitative sandwich enzyme-linked immunosorbent assay (ELISA). The primary statistical analysis involved the Spearman rank correlation test. A post-hoc power analysis was performed to contextualize the statistical findings. Results: The study population was predominantly female (95.8%), with the largest subgroup (54.2%) presenting with mild disease activity. The mean serum IL-10 concentration was 9.91±1.36 pg/mL in the mild activity group, rose to a peak of 12.22±1.95 pg/mL in the moderate activity group, and was 10.65±2.34 pg/mL in the severe activity group. The Spearman correlation test identified a weak, positive association that did not achieve statistical significance (r=0.274, p=0.059). The post-hoc power analysis confirmed the study was underpowered to definitively detect a correlation of this magnitude. Conclusion: In this cohort of Indonesian SLE patients, a statistically significant correlation between serum IL-10 levels and disease activity was not established. Given the study's methodological context, including its cross-sectional design and limited statistical power, the findings are inconclusive but hypothesis-generating. The results reinforce the profound complexity of IL-10 biology in SLE and underscore the challenges in validating it as a standalone biomarker, highlighting the need for larger, longitudinal investigations.